WITHDRAWN: Three-dimensional seismic evidence of extensive gas hydrate deposits linked with large free gas columns suggests long-range advection mechanisms. (September 2018) - Paganoni, Matteo; Cartwright, Joe A.; Van Rensbergen, Pieter
Abstract : This article has been withdrawn at the request of the author(s) and/or editor. The Publisher apologizes for any inconvenience this may cause. The full Elsevier Policy on Article Withdrawal can be found athttps://www.elsevier.com/about/our-business/policies/article-withdrawal .